The association of hereditary neuropathies and heritable skeletal disorders. Issue 834 (April 1995) - Chattopadhyay, A. K.; Kandler, R. H.; Sharrack, B.
Abstract : We describe two patients with associations of hereditary neuropathies and heritable skeletal disorders not previously reported. The first patient had Marfan's syndrome and hereditary motor and sensory neuropathy Type 1. The second patient had Ehlers-Danlos syndrome, Klippel-Feil syndrome and tomaculous neuropathy.